Research on Tensile Strength of PBT/EVA Blends - Au , Quang My; Tran , Tuong Vi; Pham , Thi Hong Nga; Huynh, Tan Quoc; Vo, Minh Trong Tin; Tran, Minh The Uyen; Nguyen, Vinh Tien; Tran, Van Tron; Vo, Xuan-Tien; Huynh, Nguyen Anh Tuan; Nguyen, Van-Thuc; Nguyen, Thanh Tan (Journal of Technical Education Science, 2023)
This research study analyzes the mechanical properties of the PBT/EVA blend. Made by adding EVA to PBT in specific proportions, the samples used for the analysis will use injection molding. The percentage of EVA added to PBT was 0%, 5%, 10%, 15%, 20%, and 25%, respectively. After pressing, the samples were measured for tensile strength according to ASTM D638 standards. The results obtained are that when the content of EVA is increased, the tensile strength of the mixture decreases gradually. Because EVA has a low vitrification temperature, adding PBT reduces the vitrification temperature of the mix and affects the tensile strength. This study is a document to develop a method of mixing materials to create a polymer mixture with suitable properties for the intended use.